Gaya Bahasa Pertentangan Pada Buku Catatan Najwa - Yulizar, Meri; Rati, Ulfa; Munawarah, Intan (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
This research is entitled "Contradictory Language Styles in Najwa's Notebook". This research was conducted to analyze what forms of conflicting language styles exist and the factors that occur. The method used in this research is a qualitative descriptive method. The data in this research are the forms of conflicting language styles and the factors that cause conflicting language styles in Najwa's Notebook. Data was obtained through several techniques, namely reading techniques and note-taking techniques. Data is analyzed by identifying data, grouping data and making conclusions. The results of the research showed that there were 20 conflicting language styles found, with 5 types of hyperbole, 7 types of sarcasm, 2 types of irony, 2types of cynicism, 4 types of climax, and 2 types of anticlimax. The factors that influence the language style in Najwa's Notebook are the time factor, the age factor, and the medium of expression.